Neutron Star Cooling - Glen, William Thomas Graham (My University, 1979)
To determine the detectability of thermal radiation from the surface of a neutron star, the surface temperature as a function of time is needed. To find this, the surface temperature as a function of core temperature is found; this ratio depending on temperature, stellar mass, and magnetic field strength. The energy loss rates from photon emission and neutrino emission are calculated, along with the specific heat of the star; the latter two quantities depending on the core temperature. The surface temperature as a function of time is then calculated for various combinations of the variable parameters: stellar mass, equation of state, magnetic field, superfluidity, and pion cutoff density. Finally, a calculation of the detectability (distance vs. age) of a typical neutron star is made, using the estimated capabilities of the X-ray telescope on the Einstein Observatory.
Keywords: neutron, star, thermal, radiation, temperature, magnetic